2009
DOI: 10.2466/pms.108.3.971-980
|View full text |Cite|
|
Sign up to set email alerts
|

Visual Search Strategies and Decision Making in Baseball Batting

Abstract: The goal was to examine the differences in visual search strategies between expert and nonexpert baseball batters during the preparatory phase of a pitcher's pitching and accuracy and timing of swing judgments during the ball's trajectory. 14 members of a college team (Expert group), and graduate and college students (Nonexpert group), were asked to observe 10 pitches thrown by a pitcher and respond by pushing a button attached to a bat when they thought the bat should be swung to meet the ball (swing judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Thus, this cognitive judgement regarding the pitcher's motion would be made in an unconscious manner and contribute to any adjustment of the swing timing. Many studies have suggested the importance to batting information about the pitcher's motion [6,7]. Our result directly supports this suggestion using virtual space.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, this cognitive judgement regarding the pitcher's motion would be made in an unconscious manner and contribute to any adjustment of the swing timing. Many studies have suggested the importance to batting information about the pitcher's motion [6,7]. Our result directly supports this suggestion using virtual space.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, Takeuchi and Inomata (2009) and Kato and Fukuda (2002) used behavioral responses and eye-tracking to monitor subject performance in judging balls and strikes between experts and novices. While the task is slightly different than ours (i.e., balls and strikes vs. fastballs, curveballs, and sliders), and our paradigm did not test experts vs. novices, the fundamental concept of a forced-choice decision based on trajectory remains the same.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, eye movements before and during pitches have been extensively studied (Shank and Haywood, 1987; Kato and Fukuda, 2002; Takeuchi and Inomata, 2009) and have been used to identify optimal visual search strategies employed by expert vs. novice players. These findings show that experts focused their visual (spatial) attention closer to the estimated release point of the pitch, when compared to novices, suggesting that early-trajectory tracking can be crucial for batting performance.…”
Section: Introductionmentioning
confidence: 99%
“…Experts' superior ability to effectively pick up early information from the opponent's movement pattern has been shown for several sports, such as badminton (Abernethy & Russell, 1987;Hagemann, Strauss, & Cañal-Bruland, 2006), tennis (Farrow, Abernethy, & Jackson, 2005;Goulet et al, 1989;Rowe & McKenna, 2001;Shim, Carlton, Chow, & Chae, 2005;Williams et al, 2002), soccer (Williams, Davids, Burwitz, & Williams, 1994), squash (Abernethy et al, 2001), cricket (Müller, Abernethy, & Farrow, 2006;Müller et al, 2009), indoor volleyball (David et al, 1990), and baseball (Takeuchi & Inomata, 2009). Furthermore, it could be shown that experts are better able to effectively interpret relative motion features of animated point-light figures (Ward, Williams, & Bennett, 2002) and to identify patterns of play based on recall and recognition processes (e.g., Williams, Hodges, North, & Barton, 2006).…”
mentioning
confidence: 96%